PERSONALIZED RETARGETING ADVERTISING AND PURCHASE INTENTION IN PREMIUM FOOTWEAR - Prima Rahadian Subakti (Jurnal Interprof, 2026)
Purpose: This study aims to examine the effect of personalized retargeting advertising (PRA) on purchase intention (PI) in the context of a premium handcrafted footwear brand in Indonesia. The study also investigates the mediating role of consumer-perceived digital advertising performance (DAP) in the relationship between PRA and PI. Research Methodology: This research used a quantitative explanatory approach with a vignette-based cross-sectional survey design. Data were collected from 200 valid respondents selected through purposive sampling from the digital community of TXTURE, a premium handcrafted footwear brand in Indonesia. The study employed a structured questionnaire using a five-point Likert scale. Data analysis was conducted using Structural Equation Modeling with Partial Least Squares (SEM-PLS) through SmartPLS 4 software. Mediation analysis was evaluated using the Variance Accounted For (VAF) method with 5,000 bootstrap resamples. Results: The findings show that personalized retargeting advertising significantly improves consumer-perceived digital advertising performance (β = 0.634, f² = 0.671, p < .001). DAP also has a significant positive effect on purchase intention (β = 0.387, f² = 0.201, p < .001). In addition, PRA directly influences purchase intention (β = 0.435, f² = 0.254, p < .001). The mediation test confirms that DAP partially mediates the relationship between PRA and PI (indirect β = 0.245; VAF = 36.0%). The structural model explains 55.3% of the variance in purchase intention. Conclusions: The study concludes that personalized retargeting advertising plays an important role in increasing purchase intention among premium footwear consumers. The direct effect of PRA on PI is stronger than the indirect effect through DAP, indicating that prior brand familiarity can directly stimulate purchase readiness without relying entirely on advertising quality evaluation. Limitations: This study is limited to a single premium footwear brand in Indonesia and uses a vignette-based cross-sectional design, which may restrict broader generalization and direct observation of actual purchasing behavior. Contributions: This study contributes to the digital advertising and consumer behavior literature by extending retargeting research into a premium high-involvement context in Indonesia. The findings also provide practical insights for premium brands in developing retargeting strategies based on audience intent, advertising quality, and personalization effectiveness.